Genetic investigation of patients with autosomal recessive ataxia and identification of two novel variants in the SQSTM1 and SYNE1 genes - Diana Mokhtari; Mohammad Jahanpanah; Nasim Jabbari; Hamed Azari; Sana Davarnia; Haleh Mokaber; Sara Arish; Rasol Molatefi; Vahid Abbasi; Behzad Davarnia (Human Genome Variation)
Abstract Hereditary ataxias are classified by inheritance patterns into autosomal dominant, autosomal recessive, X-linked, and mitochondrial modes of inheritance. A large group of adult hereditary ataxias have autosomal dominant inheritance, and autosomal recessive cerebellar ataxias (ARCAs) are rare, with greater diversity in phenotypic and genotypic features. Therefore, comprehensive genetic testing is useful for identifying the genes responsible for ARCAs. We identified two novel pathogenic variants of the SQSTM1 and SYNE1 genes via whole-exome sequencing in patients with ARCAs.